Downregulation of iNOS, IL-1β, and P2X7 Expression in Mast Cells via Activation of PAR4 Contributes to the Inhibition of Visceral Hyperalgesia in Rats - Yanli Hao; Hao Niu; Shuhong An; Ming Wang; Zhaojin Wang (Journal of Immunology Research)
Protease-activated receptor 4 (PAR4) is implicated in the inhibition of visceral hyperalgesia. In the present study, the effects of PAR4 activation on visceral hypersensitivity and expression of inflammatory mediators, including interleukin-1β (IL-1β), P2RX7 purinergic receptor (P2X7), inducible nitric oxide synthase (iNOS), and tryptase, in mast cells (MCs) were investigated via in vivo and in vitro studies. The numbers of tryptase-positive MCs with extensive PAR4, P2X7, and iNOS expression were increased in the colons of visceral hyperalgesia rats compared with controls. Intracolonic administration of PAR4-activating peptide (PAR4-AP) significantly attenuated the visceral hypersensitivity to colorectal distention and reduced the iNOS, IL-1β, P2X7, and tryptase protein and mRNA levels in the colonic mucosa. Treatment of rat bone marrow MCs (BMMCs) with PAR4-AP also reduced the iNOS, IL-1β, P2X7, and tryptase protein and mRNA levels. ERK1/2 and p38 activators (t-butylhydroquinone, tBHQ, and U-46619) reversed the suppressive effect of PAR4 activation on IL-1β and iNOS expression, whereas ERK1/2 and p38 inhibitors (PD98059 and SB203580) reversed the suppressive effect of PAR4 activation on P2X7 and tryptase expression. Our results indicate that the downregulation of inflammatory mediators, including iNOS, IL-1β, P2X7, and tryptase, in MCs that are mediated by PAR4 activation could inhibit visceral hyperalgesia via the mitogen-activated protein kinase (MAPK) signal pathway.